Tinjauan Tentang PoliEtilena (PE) - D Karyadi (Balai Besar Kimia dan Kemasan, 1997)
The application of PE is the first rank from the plastic consumption in Indonesia. Industrial structure of PE is rather strong, because the ethylene monomer as the raw material has been produced locally.The local demands of PE during the last three years (1992 - 1994) were increased very high, it on average 45, 05 % per annum. Usually the LDPE is used for film packaging material, while the HDPE is used for rigid packaging.